Mobile robot turned on by sound and directionally controlled by an external light source - Luis G. Lafaurie; Fredy E. Hoyos; Jhon E. Candelo-Becerra (Institute of Advanced Engineering and Science, 2019)
This paper presents theoretical, numerical, and experimental tests of a mobile robot, which starts on the emission of a strong sound, like an applause, and the direction and speed of the vehicle is controlled by an external pulsed light source (PWM signal). The simulation is performed in MATLAB-Simulink; electrical circuits and the experiment are shown in detail. The results show that the vehicle speed can be controlled with a PWM signal from an external light falling on the LDR sensors. Besides, the circuit was designed to consume less than 1 ampere with the four motors moving at full speed, which can easily be powered by lithium battery.